Effects of oil and global environmental drivers on two keystone marine invertebrates. Issue 1 (December 2018) - Arnberg, Maj; Calosi, Piero; Spicer, John; Taban, Ingrid; Bamber, Shaw; Westerlund, Stig; Vingen, Sjur; Baussant, Thierry; Bechmann, Renée; Dupont, Sam
Abstract Ocean warming (OW) and acidification (OA) are key features of global change and are predicted to have negative consequences for marine species and ecosystems. At a smaller scale increasing oil and gas activities at northern high latitudes could lead to greater risk of petroleum pollution, potentially exacerbating the effects of such global stressors. However, knowledge of combined effects is limited. This study employed a scenario-based, collapsed design to investigate the impact of one local acute stressor (North Sea crude oil) and two chronic global drivers (pH for OA and temperature for OW), alone or in combination on aspects of the biology of larval stages of two key invertebrates: the northern shrimp (Pandalus borealis ) and the green sea urchin (Strongylocentrotus droebachiensis ). Both local and global drivers had negative effects on survival, development and growth of the larval stages. These effects were species- and stage-dependent. No statistical interactions were observed between local and global drivers and the combined effects of the two drivers were approximately equal to the sum of their separate effects. This study highlights the importance of adjusting regulation associated with oil spill prevention to maximize the resilience of marine organisms to predicted future global conditions.